Features of Research on the Organization of Technological Lessons, Development Trends - Narimonovna, Akbarova Sayyora; Abdujalilovich, To’ychiyev Ravshan (European Journal of Life Safety and Stability (2660-9630), 2021)
the article gives an idea of skills, pedagogical skills, methods for organizing technological lessons. There is also information about the trends in the development of pedagogical technologies.